Correction of F8 intron 1 inversion in hemophilia A patient-specific iPSCs by CRISPR/Cas9 mediated gene editing - Hu, Zhiqing; Wu, Yong; Xiao, Rou; Zhao, Junya; Chen, Yan; Wu, Lingqian; Zhou, Miaojin; Liang, Desheng (Frontiers in Genetics, 2023)
Hemophilia A (HA) is the most common genetic bleeding disorder caused by mutations in the F8 gene encoding coagulation factor VIII (FVIII). As the second predominant pathogenic mutation in HA severe patients, F8 Intron 1 inversion (Inv1) completely splits the F8 gene into two parts and disrupts the F8 transcription, resulting in no FVIII protein production. The part which contains exon 2-exon 26 covers 98% of F8 coding region. We hypothesized that in situ genetic manipulation of F8 to add a promoter and exon 1 before the exon 2 could restore the F8 expression. In this study, the donor plasmid included human alpha 1-antitrypsin (hAAT) promoter, exon 1 and splicing donor site (SD) based on homology-mediated end joining (HMEJ) strategy was targeted addition in HA patient-derived induced pluripotent stem cell (HA-iPSCs) using CRISPR/Cas9 with a high efficiency of 10.19%. The iPSCs were differentiated into hepatocyte-like cells (HPLCs). The FVIII expression, secretion, and activity were detected in HPLCs derived from gene-targeted iPSCs. Thus, we firstly rescued the 140 kb reversion mutation by gene addition of a 975 bp fragment in the HA-iPSCs with Inv1 mutation, providing a promising gene correction strategy for genetic disease with large sequence variants.